Monitoring mental distress in Para athletes in preparation, during and after the Beijing Paralympic Games 2022: A 22 week prospective mixed-method study - Bentzen, M.; Kenttä, G.; Karls, T.; Fagher, K. (Frontiers in Sports and Active Living, 2022)
It is common in elite sport to monitor athletes' training load, injuries and illnesses, but mental distress is rarely included. An improved understanding of the epidemiology of mental distress among elite Para athletes and how their coaches perceive such monitoring would allow us to better develop and implement preventive measures. The purpose of this study was therefore to (1) prospectively describe elite Para athletes' mental distress, before, during and after the Beijing Paralympic Games (Paralympics Games 22 = PG22); and to (2) gain a better understanding of if and potentially how awareness of athletes' mental distress changed, through weekly monitoring, and influenced how coachers perceive athletes' mental distress and if they accounted for this before, during and after PG22. A mixed-method study design was used, in which prospective mental distress (depression and anxiety) data were collected weekly from 13 [Swedish] elite Para athletes in preparation, during and after PG22. Data were screened and evaluated weekly by a physiotherapist and a sports psychologist, and coaches also received weekly reports. A focus-group interview with the coaches were conducted post Paralympics to address coaches' awareness about mental distress and athlete health monitoring in Parasport. For data analyses, descriptive statistics was used for the quantitative data and a content analysis was conducted for the qualitative data. The results reveled the following proportion of datapoints indicating symptoms of anxiety and depression: before PG22 (15.8 and 19.1%); during PG22 (47.6 and 38.2%); and after PG22 (0 and 11.8%). The qualitative results indicated that coaches perceived athlete health monitoring as helpful for increasing their awareness of mental distress, and as a useful tool to initiate support for their athletes as well as improving their coaching. In summary, this cohort of elite Para athletes reported a high proportion of mental distress during the Winter Paralympic Games in Beijing. The results also show that it is important and feasible to monitor Para athletes' mental distress to detect and manage early symptoms of mental distress.